The influence of HfO2 additives on the optical properties of Nd3+‐doped Y2O3 ceramics. Issue 6 (2nd May 2013) - Osipov, V. V.; Orlov, A. N.; Maksimov, R. N.; Lisenkov, V. V.; Platonov, V. V.; Palashov, Oleg V.; Khazanov, Efim A.; Kravchenko, Valery B.; Fedorov, Pavel P.
Abstract Transparent yttria ceramics were fabricated by sintering a mixture of 1 at.% Nd:Y2O3 and HfO2 nanopowders produced by laser synthesis method. The best transmittance was 80.96% at the wavelength of λ=1080 nm in 6 mol.% HfO2 doped sample (1.5 mm thick). The additives of hafnium broaden both pumping and luminescence bands of Nd3+ ion in yttria ceramics. The luminescence intensity of 4F3/2→4I11/2 transition was little affected by hafnium concentration. The effective lifetime of 4F3/2 level in Nd:Y2O3 ceramics enhanced by 30% at 10 mol.% HfO2 doping concentration and the decay kinetics of laser transition attains Förster's behavior. (© 2013 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)